The integration and convergence in the information systems development – theoretical outline - Chmielarz, Witold (Integracja i konwergencja w rozwoju systemów informatycznych – szkic teoretyczny, 2011)
The main objective of this article is to present the idea of the development ofinformation systems consisting in the integration and convergence approach. It seems thatthis is a solution of classification of management information systems development problems– appearing in the literature in this field. After definitions of the main concepts used in theanalysis, the author presents the development of information systems through the prism ofthree main development paths: the increasing complexity of logical systems structure, functionalintegration and the expansion of the infrastructure of network systems. The meeting oftendencies and all the development paths occurs at a corporate level
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 43-62
Keywords: information system; integration of information systems; the development of information systems; classification and typology of information systems